2018
DOI: 10.1027/1016-9040/a000309
|View full text |Cite
|
Sign up to set email alerts
|

Religious Identity and Acculturation of Immigrant Minority Youth

Abstract: Abstract. This review proposes an integrative contextual and developmental approach to religious identity development and acculturative adaptation among adolescents with an immigrant background. Relevant research with minority adolescents has addressed three main research questions: (1) What is distinctive about religious identity development in (Muslim) minority youth? (2) How does religious identity relate to their acculturative adaptation? and (3) What is the role of interpersonal and intercultural relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 69 publications
2
57
1
Order By: Relevance
“…Our findings are consistent with other research within the United States, which revealed that most Muslim‐American youth report hyphenated identities and strong identification with both social groups (Sirin & Fine, ; Tahseen & Cheah, ). These findings contrast those of existing European studies, which tend to report negative associations between minority‐group identities (e.g., religious and ethnic) and mainstream national identities, indicating identity incompatibility in these sociocultural contexts (e.g., Fleischmann & Phalet, ; ). Muslim‐American adolescents may be more likely to identify strongly with both their religious and the mainstream national group because hyphenated identities are more accepted and common in the United States context, which has historically been more tolerant and accepting of immigrants and diversity than European countries (e.g., Verkuyten & Martinovic, ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings are consistent with other research within the United States, which revealed that most Muslim‐American youth report hyphenated identities and strong identification with both social groups (Sirin & Fine, ; Tahseen & Cheah, ). These findings contrast those of existing European studies, which tend to report negative associations between minority‐group identities (e.g., religious and ethnic) and mainstream national identities, indicating identity incompatibility in these sociocultural contexts (e.g., Fleischmann & Phalet, ; ). Muslim‐American adolescents may be more likely to identify strongly with both their religious and the mainstream national group because hyphenated identities are more accepted and common in the United States context, which has historically been more tolerant and accepting of immigrants and diversity than European countries (e.g., Verkuyten & Martinovic, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite drastic increases in religious discrimination, hate crimes, and terror attacks targeting religious minorities in Western contexts (CAIR, ; FBI, ), studies examining the impact of discrimination based on religious group membership are scant. Preliminary research indicates that religious discrimination is particularly harmful for individuals’ mental health perhaps because it threatens one's religious group identity, which is particularly salient for religious minority youth given that it carries an “eternal significance” and is attached to a sacred and highly appraised belief system (e.g., Fleischmann & Verkuyten, forthcoming; Phalet, Fleischmann, & Hillekens, ; Ysseldyk, Matheson, & Anisman, ). Hence, Muslim‐American adolescents may be at risk for psychological difficulties and mental health problems because they are members of a socially devalued religious minority group and face discrimination on an individual level in their interpersonal relationships (e.g., having hijab pulled off, being called a terrorist) and are also exposed to anti‐Muslim rhetoric and public stigma against Muslims as a group in the form of Islamophobia (Abu‐Ras, Suárez, & Abu‐Bader, ; Husain & Howard, ; Ocampo et al., ).…”
Section: Discrimination and Internalizing And Externalizing Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…These youngsters are also bound to develop a sense of belonging to the country in which they are raised, or have been born and spent most of their lives (Verkuyten & Martinovic, 2012). In addition, religious identity is an important facet of minority youths' social identity as religion often is strongly entwined with migrants' heritage culture and is considered among the core cultural elements that migrant parents aim to transmit to the next generation (Phalet, Fleischmann, & Hillekens, 2018). Although the importance of these different social identities for minority youth is widely recognized and previous work studied their development among youth (e.g., Umaña-Taylor et al, 2014), little research examines the development of these social identities in conjunction.…”
mentioning
confidence: 99%